2016
DOI: 10.1155/2016/2371970
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Postsynaptic Compartment of Excitatory Synapses by the Actin Cytoskeleton in Health and Its Disruption in Disease

Abstract: Disruption of synaptic function at excitatory synapses is one of the earliest pathological changes seen in wide range of neurological diseases. The proper control of the segregation of neurotransmitter receptors at these synapses is directly correlated with the intact regulation of the postsynaptic cytoskeleton. In this review, we are discussing key factors that regulate the structure and dynamics of the actin cytoskeleton, the major cytoskeletal building block that supports the postsynaptic compartment. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 234 publications
(285 reference statements)
1
16
0
Order By: Relevance
“…It has been shown that Camk2a may interact with several proteins, e.g. Grin2b [ 37 ] and Camk2b, the second most abundant Camk2 isoform, may associate with fibrillar actin and regulate actin filaments stability [ 38 ] which, in turn, regulates the organization of the postsynaptic regions in glutamatergic synapses [ 39 ]. Our proteomic analysis revealed that the total Camk2 amount in hippocampus and cerebellum was statistically significantly decreased by aging ( Figure 3A and B , Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that Camk2a may interact with several proteins, e.g. Grin2b [ 37 ] and Camk2b, the second most abundant Camk2 isoform, may associate with fibrillar actin and regulate actin filaments stability [ 38 ] which, in turn, regulates the organization of the postsynaptic regions in glutamatergic synapses [ 39 ]. Our proteomic analysis revealed that the total Camk2 amount in hippocampus and cerebellum was statistically significantly decreased by aging ( Figure 3A and B , Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on their turnover rate, actin filaments can be divided into dynamic and stable pools and based on the morphology described as linear or branched filaments. The controlled assembly and tread milling of F‐actin are essential for plasticity and stability of synapses (MacGillavry et al, ; Mikhaylova et al, ; Mundhenk, Fusi, & Kreutz, ; Stefen et al, ). Importantly, a plethora of actin nucleation factors, severing, and capping proteins are involved in filament formation and regulation of filament stability (Hotulainen & Hoogenraad, ).…”
Section: Synaptic Actin Cytoskeletonmentioning
confidence: 99%
“…The controlled assembly and tread milling of F-actin are essential for plasticity and stability of synapses (MacGillavry et al, 2016;Mikhaylova et al, 2018;Mundhenk, Fusi, & Kreutz, 2019;Stefen et al, 2016). Importantly, a plethora of actin nucleation factors, severing, and capping proteins are involved in filament formation and regulation of filament stability (Hotulainen & Hoogenraad, 2010).…”
Section: Synaptic Actin Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dendritic arborization of neurons could also be regulated by arranging the cytoskeleton components (Ka and Kim, 2016). It is clear that actin-rich cytoskeletal proteins contribute to the specialized dendritic protrusions that provide structural support (Stefen et al, 2016). Therefore, we hypothesized that the disturbed neuron morphology resulting from miR-194 overexpression probably originates from the disordered F-actin.…”
Section: Discussionmentioning
confidence: 99%